How does a shared decision-making (SDM) intervention for oncologists affect participation style and preference matching in patients with breast and colon cancer? - Bieber, Christiane; Nicolai, Jennifer; Gschwendtner, Kathrin M.; Müller, Nicole; Eich, Wolfgang (Journal of cancer education, 2018)
The aims of this study are to assess patients’ preferred and perceived decision-making roles and preference matching in a sample of German breast and colon cancer patients and to investigate how a shared decision-making (SDM) intervention for oncologists influences patients’ preferred and perceived decision-making roles and the attainment of preference matches. This study is a post hoc analysis of a randomised controlled trial (RCT) on the effects of an SDM intervention. The SDM intervention was a 12-h SDM training program for physicians in combination with decision board use. For this study, we analysed a subgroup of 107 breast and colon cancer patients faced with serious treatment decisions who provided data on specific questionnaires with regard to their preferred and perceived decision-making roles (passive, SDM or active). Patients filled in questionnaires immediately following a decision-relevant consultation (t1) with their oncologist. Eleven of these patients’ 27 treating oncologists had received the SDM intervention within the RCT. A majority of cancer patients (60%) preferred SDM. A match between preferred and perceived decision-making roles was reached for 72% of patients. The patients treated by SDM-trained physicians perceived greater autonomy in their decision making (p < 0.05) with more patients perceiving SDM or an active role, but their preference matching was not influenced. A SDM intervention for oncologists boosted patient autonomy but did not improve preference matching. This highlights the already well-known reluctance of physicians to engage in explicit role clarification.Trial Registration: German Clinical Trials Register DRKS00000539; Funding Source: German Cancer Aid.
Gesehen am 20.08.2019
Published online: 13 December 2016